PP-054 Stability study of 100 mg/ml paediatric pyrazinamide oral suspension in syrspend. (25th February 2017) - Boivin, PN; Geffroy, C; Tron, C; Luans, C; Lester, MA
Abstract : Background: Pyrazinamide is an antituberculosis agent used in adjunctive treatment of tuberculosis infection in combination with other antituberculosis agents, such as isoniazid, rifampicin and ethambutol. The tablet form is unsuitable for paediatric patients and the pharmacist needs to produce an oral suspension. Data on pyrazinamide stability in an oral suspension are scarce and were produced several decades ago. Thus new stability information is needed. Purpose: The aim of this study was to determine the stability of 100 mg/mL pyrazinamide oral suspension in commercial compounding excipient Syrspend SF PH4 (FAGRON). Material and methods: 3 batches of oral suspensions were prepared, using pyrazinamide tablets and Syrspend SF-PH4, packaged in amber vials to protect from light, and stored at room temperature. Several parameters were studied on days 0, 3, 5, 8, 15, 30, 60 and 90 (n=3): physical stability (visual inspection, osmolality measurements) and chemical stability (pH measurement, residual concentrations of pyrazinamide, degradation products identification). Pyrazinamide concentrations were determined using a validated analytical method based on high performance liquid chromatography with UV detection at 280 nm. Chromatographic separation of the analytes was performed with a WATERS C18 ATLANTIS T3 column (150×4.6 mm, 5 μm). The mobile phase was composed of acetonitrile/phosphate buffer at pH 3 (40:60 v/v) and flow rate was adjusted at 1 mL/min. Data were acquired and processed with EMPOWER Software. Microbiological stability was checked according to the test using colony counts on media platings. Results: No change in physical properties was observed during the study period. Drug concentration remained within ±5% of nominal values over 90 days and no degradation products appeared on the chromatograms. Microbiological media plates remained free from any bacterial or fungal colony. Conclusion: This study showed that 100 mg/mL pyrazinamide oral suspension in Syrspend SF PH4 was stable for at least 90 days at room temperature, so we determined a shelf life of 90 days for this preparation. Further study, using a mass spectrometer method, will be conducted to confirm this shelf-life. References and/or acknowledgements: Methodological guidelines for stability studies of hospital pharmaceutical preparations. ICH Guidelines . No conflict of interest